Pengaruh Perceived Quality dan Perceived Value terhadap Customer Satisfaction pada Photograms Studio di Tunjungan Plaza Surabaya - Mayang Puspita Amara; Rina Dewi; Bambang Karnain; Harsono Teguh Santoso; Achmad Daengs GS (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to test and analyze the effect of perceived quality, perceived value on customer satisfaction with a sample of 100 respondents using purposive sampling as a sampling technique. Data collection using questionnaire techniques that are distributed using online google forms. Data analysis in this study multiple linear regression analysis, descriptive analysis, data normality test, hypothesis testing and determination coefficient test. The results showed that the variable perceived quality (X1) has a significant effect on customer satisfaction (Y) with the results of the hypothesis test showing t count> t table (10.626 > 1.985). The variable perceived value (X2) has no significant effect on customer satifcation (Y), because the hypothesis test results show t count < t table (0.365 < 1.985). The variables perceived quality (X1) and perceived value (X2) together affect customer satisfaction (Y) with a calculated F value of 171,224 and a significance value of 0.00 which is smaller than the maximum significance limit of 0.05. The implication of this research is to increase perceived value at photograms studio tunjungan plaza Surabaya.